Analisis Kasus tentang Dampak Penggunaan ChatGPT terhadap Pemahaman Konsep Matematika Siswa Kelas XI MA Aisyiyah Sungguminasa (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to examine in depth the impact of using ChatGPT as a supporting learning medium on the conceptual understanding of mathematics among eleventh-grade students at MA Aisyiyah Sungguminasa. The background of this research arises from the low level of students’ comprehension of mathematical concepts, as reflected in frequent mistakes in solving problems, difficulties in connecting one concept to another, and a lack of confidence in problem-solving. This condition indicates the need for innovative learning approaches that can provide more interactive, detailed, and easily understood explanations for students. The research method employed was descriptive qualitative with a case study approach. The research subjects consisted of eleventh-grade students who utilized ChatGPT in learning mathematics, particularly on the topics of functions and quadratic equations. Data collection techniques included direct classroom observation, in-depth interviews with students and teachers, and analysis of students’ work produced with the assistance of ChatGPT. The findings revealed that the use of ChatGPT had a positive impact on improving students’ understanding of mathematical concepts. Students became more capable of grasping fundamental ideas, following systematic steps in problem-solving, and applying mathematical concepts in different contexts. Moreover, ChatGPT fostered independent learning, increased curiosity, and encouraged the development of students’ critical thinking skills. Nevertheless, challenges were also identified, such as students’ potential dependency on the application and the risk of misinterpretation without proper guidance. Therefore, the integration of ChatGPT into learning should be carried out under the supervision of teachers to ensure that learning outcomes are more effective, optimal, and sustainable.